Russian writers and the fin de siecle : the twilight of realism - Bowers, Katherine; Kokobobo, Ani (Cambridge university press, 2015)
Argues that the gloomy mood associated with degeneration theory, biodeterminism, Freudian psychoanalysis, and apocalypticism in Europe had appeared in works by Turgenev, Dostoevsky, and Tolstoy well before the end of the 19th century.